Emergent Uric Acid Treatment is Synergistic with Mechanical Recanalization in Improving Stroke Outcomes in Male and Female Rats. (15th September 2018) - Aliena-Valero, Alicia; López-Morales, Mikahela A.; Burguete, María C.; Castelló-Ruiz, María; Jover-Mengual, Teresa; Hervás, David; Torregrosa, Germán; Leira, Enrique C.; Chamorro, Ángel; Salom, Juan B.
Graphical abstract: Highlights: The effects of uric acid in an ischemic stroke model relevant to mechanical thrombectomy treatment were assessed. At 24 h after stroke, neurofunctional impairment and infarct were reduced in male and female rats by uric acid treatment. Beneficial effects of uric acid were better manifested in brain cortex after postischemic hyperperfusion. After a 7-day follow-up, male rats subjected to uric acid treatment still showed improved outcomes. Additional clinical testing of uric acid as an adjunctive treatment to mechanical thrombectomy is warranted. Abstract: Preclinical and clinical studies support a promising, albeit not definitive, neuroprotective effect of emergent uric acid (UA) administration in ischemic stroke. We assessed the effects of UA in an ischemic stroke model relevant to the current treatment paradigm of mechanical thrombectomy within the STAIR/RIGOR recommendations. A cohort of male and female Wistar rats was subjected to ischemic stroke with mechanical recanalization under physiological monitoring. The effects of transient middle cerebral artery occlusion (tMCAO) with adjunctive UA (IV, 16 mg/kg) or vehicle treatment were assessed at 24 h and 7 days. Outcomes included neurofunctional impairment, brain infarct (TTC staining, MRI imaging and cresyl violet staining) and edema. At 24 h after tMCAO, neurofunctional scores and brain infarct were significantly reduced in rats subjected to UA treatment compared to vehicle, with a selective effect of UA on cortical infarct. No differential effect of UA between male and female rats was evidenced, as no significant interaction of sex with stroke outcomes was found. Rats achieving higher reperfusion levels after tMCAO showed superior reduction of neurofunctional impairment, cortical infarct and edema by UA. After a 7-day follow-up, male rats subjected to UA treatment still showed reductions in neurofunctional impairment and infarct size, compared to vehicle treatment. In conclusion, UA treatment immediately after transient ischemia results in a sex-independent, maintained reduction of brain damage and neurological impairment, better manifested in hyperperfusion conditions. This synergistic effect of UA with mechanical recanalization supports additional clinical testing of UA as an adjunctive treatment to mechanical thrombectomy.